Use of shredded empty fruit bunch and cement block debris as a media for Brassica rapa var. chinensis cultivation - Mohd Roslim, Muhammad Huzaifah (2015)
Oil palm empty fruit bunch (EFB) and cement brick debris (CBD) could serve as an alternative media for crops. Malaysia generates large quantities of agricultural wastes from the oil palm plantations and huge volumes of construction waste materials due to rapid urbanization. The CBD is one of the waste products that can be used as a medium for growing crops. This study is specifically focused on the potential of using shredded EFB and CBD as a medium with different ratios for growing mustard (Brassica rapa var. chinensis). The objective of this study was to characterise new growth media using shredded EFB and CBD. Four types of media ratios as treatments were used; soil: EFB: CBD (1:1:1, 1:1:2, 0:1:2, 0:1:1) and standard medium ratio (3:2:1) which is a control. The experimental treatments were arranged in complete randomised design (CRD) with six replicates. The variables measured were pH, EC, water retention, soil moisture, bulk density and tissue nutrients such as potassium (K), calcium (Ca) and magnesium (Mg). The yield and growth of mustard was also recorded overtime. Atomic absorption spectrophotometer (AAS) was used to measure nutrients concentration. The result showed that shredded EFB, CBD and soil at all ratios above can be used as a new growth medium for Pak Choy cultivation. In addition, more research work should be done to improve and identify the suitable ratio because of the medium ratios in this study having higher pH and excessive in Ca content which can give impact to the medium.